Optimasi bubuk bunga telang, enzim transglutaminase, dan bread improver untuk meningkatkan fungsionalitas dan kualitas roti manis [Optimizing the butterfly pea powder, transglutaminase enzyme, and bread improver to improve the functionality and quality of sweet bread] - Endah Wulandari; Safri Ishmayana; Herlina Marta; Muhammad Fadhlillah; Nurisa Fadillah Isnaeni (Jurnal Teknologi & Industri Hasil Pertanian, 2022)
Sweet bread with moderate functional properties can be enhanced with tertiary function by adding telang flower, a natural ingredient rich in antioxidants, natural blue in color derived from anthocyanins. In addition, bread volume enhancers, such as transglutaminase enzymes and bread improvers are also needed to improve the quality of bread. The purpose of this study was to determine the optimum formulation of telang flower sweet bread using Response Surface Method (RSM)-Central Composite Design (CCD) with telang flower powder (2-6%), transglutaminase enzyme (0.027-0.083 U/g protein), and breading agent (3-9 U/g flour) as an independent variable, and produces a response in the form of specific volume and antioxidant activity. The optimum formula was obtained with a combination of 4.71% telang flower powder formula, transglutaminase enzyme 0.055 U/g flour protein, and 5.23 U/g flour bread improver which resulted in a specific volume of 3.15 ± 0.05 cm3/g and activity antioxidant amounted to 388.372 ± 13.11%. The characteristics of the optimum bread had firmness values of 629.77±39.23 g.f, springiness 42.14±0.87%, sweet bread crumbs were dark blue, but the butterfly  pea flower sweet bread's quality was not as well accepted as the control sweet bread with the exception of how the bread feels when bitten.